Evaluation of complex systems: multicriteria approach - Voronin, A.; Savchenko, A. (Проблемы управления и информатики, 2022)
The quality of an object's functioning is assessed by a set of properties that are quantitatively expressed (quality criteria). The selection of properties, carried out by the decision-maker (DM), represents a decomposition, resulting in a hierarchical structure. In decision theory, the case where the multi-criteria problem is represented by a two-level hierarchical system is the most elaborated. In this case, the task of evaluating (combining the criteria of) a simple object is usually solved using a single scalar folding mechanism of the vector criterion. The numerical value of the folding is the overall evaluation of the quality of the object's functioning. However, even with a three-level hierarchy, the object is considered complex, and its evaluation requires other approaches. It is shown that any vector evaluation task of an object can be represented by a hierarchical system of criteria obtained as a result of decomposing the object's properties. Якість функціонування обʼєкта оцінюється сукупністю властивостей, що мають кількісне вираження (критерії якості). Вибір властивостей обʼєкта, який здійснюється особою, що приймає рішення (ОПР), являє собою декомпозицію, в результаті якої утворюється ієрархічна структура. У теорії прийняття рішень найбільш детально розроблено випадок, коли багатокритеріальна задача представлена дворівневою ієрархічною системою. Тут задача оцінки (композиції критеріїв) простого обʼєкта зазвичай розвʼязується за допомогою механізму одиничної скалярної згортки векторного критерію. Числове значення згортки є оцінкою якості функціонування даного обʼєкта в цілому. Але навіть при трирівневій ієрархії обʼєкт розглядається як складний і його оцінка вимагає інших підходів. Показано, що будь-яка задача векторної оцінки об’єкта може бути представлена ієрархічною системою критеріїв, отриманих у результаті декомпозиції властивостей об’єкта.